Liming in the transition to no-till under a wheat-soybean rotation - Costa, Antonio; Rosolem, Ciro Antonio [UNESP] (Elsevier B.V., 2007)
Soil and subsoil aluminium toxicity has been one of the main limiting factors for soybean and wheat yields in tropical soils. Usually liming is the most effective way to deal with soil acidity and Al toxicity, but in no-till systems the soil is not disturbed making it impossible to incorporate lime in the arable layer, and lime has been usually applied on the soil surface. In this paper soybean and wheat responses to lime applied on the soil surface and/or incorporated in the soil arable layer were evaluated during the transition from conventional tillage to a no-till system. The experiment was conducted for 3 years in Parana, Brazil, using a wheat-soybean rotation. Lime rates ranging from 0.0 to 9.0 t ha(-1) were incorporated down to 20 cm and 4.5 t ha(-1) were spread or not on the soil surface. Soil samples were taken down to 60 cm, 39 months after the first lime application. Soil chemical characteristics were affected by lime application down to 60 cm deep in the profile. Soybean responded to lime irrespective of application method, but the highest accumulated yield was obtained when lime was incorporated into the arable layer. For wheat, the more sensitive the cultivar, the greater was the response to lime. During the introduction of a no-till system, lime must be incorporated into the arable layer when the wheat cultivar is Al-sensitive. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: aluminium; base leaching; calcium; magnesium; organic acids